Penyusunan Pola Aktivitas Pembelajaran Bahasa Inggris dan Perspektif Mahasantri Terhadap Penguasaan Bahasa Inggris di Era Revolusi Industri 4.0 - Tri Ilma Septiana; Bustomi Ibrohim (Tazkiya, 2021)
This study was conducted to design an applicable pattern of English learning activities for students at Ma'had Al-Jami'ah Sultan Maulana Hasanuddin Banten and explore their perspective on the urgency of mastering English after entering the Industrial Revolution Era 4.0 including outlining the driving factors and barriers to learn English. This study used an ethnography approach by collecting data through various instruments such as in-depth interviews, direct observation, and focus group discussions. The findings of this study reveal that the pattern of English learning activities can be applied in Ma'had Al-Jami'ah Sultan Maulana Hasanuddin Banten, among others: (1) the application of the English Zone in the dormitory environment; (2) holding an English speech; (3) making a vocabulary board; (4) holding morning conversations and (5) forming a language driving team. Furthermore, the perspective of the students towards learning English is very good because they believe that English is very useful to support their studies, especially in doing assignments, for interview purposes when applying for jobs and for continuing studies abroad. Some factors that encourage students to learn English include: (1) The high motivation of the students in participating in English training; (2) The students' awareness of the importance of mastering English; (3) There is support from the chairman of Ma'had Al-Jami'ah Sultan Maulana Hasanuddin Banten; (4) the availability of representative classrooms for learning English; and (5) the desire of musyrif (caretaker) and santri to improve foreign language skills, both Arabic and English. This is shown by forming a language driving team and programs to improve foreign language skills.